THE INFLUENCE OF SELF-DEVELOPMENT, SCHOOL ORGANIZATIONAL CULTURE, AND WORK ENVIRONMENT ON TEACHER PERFORMANCE AT SMP NEGERI 1 JABON SIDOARJO - If’alul Naufal; Onik Farida Ni’matullah; Yuli Ifana Sari (Antis Publisher, 2026)
Objective: This study aims to analyze the influence of self-development, school organizational culture, and work environment on teacher performance at SMP Negeri 1 Jabon. Method: The research method used is quantitative with a descriptive correlational approach. The research sample consisted of 42 teachers selected using random sampling techniques. The research instrument was a questionnaire with a Likert scale. Data analysis used multiple linear regression to test the simultaneous and partial influence of the three independent variables on teacher performance. Results: The results showed that self-development, school organizational culture, and work environment simultaneously had a significant effect on teacher performance, with a significance value of 0.000. While partially, the self-development variable had a significant effect on teacher performance with a value of 0.10 < 0.05 and a calculated T value of 2.710 > 2.024. The school organizational culture variable did not have a significant effect on teacher performance with a value of -0.36 < 2.024 and a calculated T value of 0.971 > 0.05. The work environment variable significantly influences teacher performance with a value of 0.02 > 0.05 and a calculated T value of 3.250 > 2,024. Novelty: The implications of this study provide recommendations for schools to strengthen teacher self-development programs and create a conducive work environment to improve performance.